2020
DOI: 10.1111/jce.14531
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of pulmonary vein isolation guided by the ablation index: 1‐year outcome of the AIR registry

Abstract: Background Ablation index (AI) is a new lesion quality marker that has been demonstrated to allow a high single‐procedure arrhythmia‐free survival in single‐center studies. This prospective, multi‐center study was designed to evaluate the reproducibility of pulmonary vein (PV) isolation guided by the AI. Methods A total of 490 consecutive patients with paroxysmal (80.4%) and persistent AF underwent first time PV isolation and were divided in four study groups according to operator's preference in choosing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 19 publications
3
23
0
Order By: Relevance
“…Several observations testify to the reliability of the reported >90% single‐procedure freedom from paroxysmal AF after ‘CLOSE’‐guided PVI: avoiding weak links within the RF circle deployed is the key to durable PV isolation and clinical success 17–20 . Moreover, in a multicenter clinical practice setting, an ablation protocol that respected strict criteria for contiguity and the quality of lesions resulted in a high rate of 1‐year freedom from AF recurrence and a low complication rate, irrespective of the ablation catheters used and the AI settings 21,22 …”
Section: Discussionmentioning
confidence: 92%
“…Several observations testify to the reliability of the reported >90% single‐procedure freedom from paroxysmal AF after ‘CLOSE’‐guided PVI: avoiding weak links within the RF circle deployed is the key to durable PV isolation and clinical success 17–20 . Moreover, in a multicenter clinical practice setting, an ablation protocol that respected strict criteria for contiguity and the quality of lesions resulted in a high rate of 1‐year freedom from AF recurrence and a low complication rate, irrespective of the ablation catheters used and the AI settings 21,22 …”
Section: Discussionmentioning
confidence: 92%
“…Several other ongoing studies, including a multicenter trial, are evaluating the efficiency, safety, and efficacy of the CLOSE protocol 13,14 . A recent study, however, suggested that an AI value of 330 for the posterior and 450 for the anterior wall were as safe and reliable as higher values (380 for the posterior and 500 for the anterior wall) 15 …”
Section: Discussionmentioning
confidence: 99%
“…One of the STAI studies reported 67% (n = 21) of patients underwent cavotricuspid isthmus ablation or left atrial posterior wall ablation with a box lesion set [6]. One study reported 8% (n = 3) of patients received cavotricuspid isthmus ablation [7]; in the other study, one patient with PsAF received a posterior wall box lesion [12]. In contrast, three of the CB studies reported using a PVIonly approach [4,19,20], and one reported 7.9% (n = 8) of patients underwent right atrial flutter ablations using RF energy [18].…”
Section: Discussionmentioning
confidence: 99%
“…Individual patient-level data from four investigator-initiated studies on STAI that included patients with PsAF were available for analysis [6][7][8]12]. The first study by Hussein et al [6] was a prospective, single-arm registry that included 40 PsAF patients.…”
Section: Identification Of Studies For Maic Analysesmentioning
confidence: 99%
See 1 more Smart Citation